Towards another ontology of performance - Akıncı, Eylül Fidan. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2013., 2013)
This thesis focuses on the concept of performance, specifically in its artistic modality, as a reflexive event through which an ontological examination of being can be actualized. Starting from a critique of current positioning of contemporary performance theory against mimetic structures, the thesis tries to negotiate the eventbeing of performance with its foundation on repetition and representation. French philosopher Jacques Derrida’s critique of Western metaphysics on the basis of the philosophy’s attack on writing and literature deeply informs and structures the thesis’ critique of performance theory and its claims to presence, liveness and truth of the unmediated. In the final analysis, the thesis tries to read how performance is also coopted by the media culture and art system it has initially criticized.
Keywords: Performance art.